Faktor-Faktor yang Mempengaruhi Tingkat Kepuasan Nasabah Bank Rakyat Indonesia (BRI) Cabang Samarinda 1 - Chottam Chottam; Achmad Rudzali; Florentina Kohat (Politeknik Negeri Samarinda, 2022)
The purpose of this study was to test customer satisfaction with the role of customer service partially and simultaneously at PT Bank Rakyat Indonesia Samarinda Branch Office 1. The data collection instrument was a questionnaire measured by a Likert scale. The sample in this study was 350 customers of PT Bank Rakyat Indonesia Samarinda Branch Office 1 who were randomly assigned using probability sampling techniques. The results of the two hypotheses indicate that the variable role of customer service (X) is proven to have a positive and significant effect on customer satisfaction (Y) at PT Bank Rakyat Indonesia Samarinda Branch.